Cation order and disorder in cathode materials for Li-ion batteries - Yue Zhou; Jiaqiang Huang; Biao Li (Next Materials)
Design of cathode materials has been the central topic of Li-batteries since its invention. Beyond chemical composition, another dimension of the material design resides at crystal structures where factors like ionic size, coordination environment, and superstructure play significant roles. In this review, we shift to another focus, i.e. cation order and disorder, that has been prevailing in recent years in the field of cathode materials, to overview how this structural feature emerges to govern the cathode electrochemistry. We begin with a broad conceptualization of cation order and disorder across various scales, followed by an examination of the thermodynamic and kinetic factors that underlie their formation. We then revisit how cation order and disorder evolve along with cycling that is crucial in determining the cycle life of cathode materials. The roles of cation order and disorder on various aspects of electrochemistry, such as Li diffusion, cycling stability, anionic redox activity, voltage profile and voltage hysteresis, are subsequently summarized and discussed. We lastly extend our review to paying attention on the experimental tailoring and characterizing of cation arrangement in cathodes that are pivotal for future cathode design.